The effect of complement factor B gene variation on age-related macular degeneration in Iranian patients - Roshanipour, Nasrin; Bonyadi, Morteza; Jabbarpour Bonyadi, Mohammad Hossein; Soheilian, Masoud (Iranian journal of ophthalmology, 2019)
To determine the possible association of rs4151667 (L9H) complement factor B (CFB) gene with age-related macular degeneration (AMD). The L9H is one of the functional variations of the CFB. CFB gene encodes the most important protein of the complement system. Two hundred sixty-six patients with AMD and 194 unrelated age/sex-matched controls were genotyped for CFB gene (rs4151667) using the polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) method. All research subjects were selected from three regions of Iran (Tehran, Tabriz, and Gonabad). The results showed a significant difference between the frequency of non-TT genotype in total patients and controls [odds ratio (OR) = 0.424, P = 0.038]. The analysis for each studied region showed that in patients originating from the Gonabad population, the frequency of TT and non-TT genotypes between patients and the control group were significantly different (OR = 2.894, P = 0.046 for TT genotype and OR = 0.346, P = 0.026 for non-TT genotype). In patients originating from Tabriz population, TT and non-TT genotypes and A allele revealed considerably different frequencies between the patient and control groups (OR = 3.043, P = 0.017; OR = 0.329, P = 0.013 and OR = 0.347, P = 0.048, respectively). Analysis of patients from Tehran also showed that there was a significant difference in the frequency of TT genotype between patients and controls (OR = 2.168, P = 0.04). The results of the current study indicated a possible protective role for non-TT genotype in L9H variation CFB gene against AMD in a sample of the Iranian population. The region segregation results showed that TT genotype might be a risk factor for susceptibility to AMD.